Preliminary Investigation into Measurement While Drilling as a Means to Characterize the Coalmine Roof - Manoj Khanal; Johnny Qin; Baotang Shen; Bongani Dlamini (Resources, 2020)
The variable nature of the coalmine roof poses a challenge to roadway stability during underground coal mining. There have been fatalities and financial losses in the coal mining industry due to roadway failures and roof falls. Generally, the geotechnical and geological data gathered from exploration boreholes, which are drilled at considerable distances from each other, are used to characterize the thickness and quality (including strength) of the coalmine roof. This process provides a limited number of samples that cannot represent the discontinuous nature of the strata in the coalmine roof nor can they form reliable inputs to a digital model of the rock mass component of the digital mine. Gaining confidence in the strata properties of the coalmine roof is necessary for the modelling, design, and maintenance of roadways. The paper describes the progress of the ongoing work to investigate the monitoring while drilling (MWD) concept for characterizing coalmine roofs. Large-scale drilling experiments in synthesized sandwiched rock samples without interfaces were carried out. The drilling response data were analyzed to identify whether the drill data differentiates the various strengths associated with the rock samples. The initial results show that the drilling data can differentiate the synthesized rock samples.